High-energy gamma-ray production in microquasars - Christiansen, Hugo (2007)
A hadronic model for gamma-ray production in microquasars is presented. Microquasars are galactic binary systems with jets, which have, presumably, hadronic components. We consider a microquasar formed by a neutron star that accretes matter from the equatorial wind of a Be primary star. The collision between the jet, emitted by the compact object, and the dense equatorial disk of the companion massive star is responsible for the gamma-ray production. Gamma-rays result from the decay of neutral pions produced in relativistic pp interactions arising from this collision all along the orbit. Assuming a simple, positional independent set of parameters, our calculations are consistent with a peak of gamma-ray flux at the periastron passage with a secondary maximum near apastron. Under this assumption, gamma-ray signals would be in contrast with the radio/X-ray outbursts which peak clearly after periastron. We finally calculate the opacity of the ambient photon field to the propagation of the gamma-rays. The spectral energy distribution appears strongly attenuated in a wide band (50 GeV - 50 TeV) due to local absorption. These spectral features should be detectable by an instrument like MAGIC through exposures integrated along several periastron passages.